2015
DOI: 10.3390/w7084523
|View full text |Cite
|
Sign up to set email alerts
|

Forms of Nutrients in Rivers Flowing into Lake Chaohu: A Comparison between Urban and Rural Rivers

Abstract: Nutrient inputs from rivers play an important role in lake eutrophication. To compare the forms characteristics of phosphorus (P) and nitrogen (N) in rivers flowing through rural and urban areas, water samples were collected seasonally from five urban rivers and six rural rivers flowing to Lake Chaohu, China. Higher total phosphorus (TP), particulate phosphorus (PP), soluble reactive phosphorus (SRP), and dissolved nonreactive phosphorus (DNP) concentrations and SRP/TP percentages were observed in urban rivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Although the lakes of the Babant River accumulate nitrogen, phosphorus is transported outside the system, which the authors explained by the internal enrichment of this component [29]. In catchments dominated by anthropogenic activity, nitrogen in the ammonium form dominates; its source is mainly wastewater [36]. In fluvio-lacustrine systems, it is very important to predict the system's response to increased nutrient loading [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although the lakes of the Babant River accumulate nitrogen, phosphorus is transported outside the system, which the authors explained by the internal enrichment of this component [29]. In catchments dominated by anthropogenic activity, nitrogen in the ammonium form dominates; its source is mainly wastewater [36]. In fluvio-lacustrine systems, it is very important to predict the system's response to increased nutrient loading [1].…”
Section: Discussionmentioning
confidence: 99%
“…In many urban rivers, discharge from wastewater treatment plants and industrial processes create nutrient hot spots which significantly alter the overall water quality in these systems (Carey & Migliaccio, 2009; Luthy et al, 2015; McClain et al, 2003). Elevated concentrations of nitrogen, especially ammonia (NH 3 ), nitrate (NO 3 − ), and nitrite (NO 2 − ) (Groffman et al, 2004; Larned et al, 2016; Schoonover et al, 2005) and phosphorus, including total phosphorus (TP) and orthophosphate (PO 4 3− ) (Carpenter et al, 1998; Nagy et al, 2012; Zhang et al, 2015) have been observed in many urban rivers. In addition, elevated biochemical oxygen demand (BOD) and decreased dissolved oxygen (DO) are commonly associated with point source pollution in urban areas (Magdaleno et al, 2001; Olatunde et al, 2015; Rice & Bridgewater, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of the three sites located in Chaohu, water content, LOI, TP, and TN were the lowest at MC, while higher values were detected at the WC and EC sites. This is because large amounts of pollutants from Hefei City and Feixi County have been discharged into WC through the NF, SW, TX, and PH rivers, resulting in serious eutrophication and harmful algae blooms in western Chaohu [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%